Compounds Isolated from the Ethyl Acetate Fraction of the Aerial Parts of Oxalis corniculata L. - Loi, Vu Duc; Nga, Dang Thi Quynh; Huong, Do Thi Mai; Huy, Nguyen Quoc (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 34 No 1, 2018)
The ethyl acetate fraction of the aerial parts of Oxalis corniculata L. (collected in Ha Tinh province) isolated three compounds (1-3) by chromatographic methods. Their structures were elucidated by spectroscopic methods, including MS and NMR. These compounds were identified as: Eburicoic acid (1); 24-methylenecholest-4-ene-3β, 6β-diol (2); and 3β-hydroxylanosta-8.24-dien-21-oic acid (3). These compounds were, for the first time, isolated from the aerial parts of Oxalis corniculata L. Keywords Oxalis corniculata, eburicoic, 24-methylenecholest-4-ene-3β, 6β-diol, 3β-hydroxylanosta8,24-dien-21-oic. References Iqbal Hussain, Muhammad Imran, Nusrat Hussain, Amjad Hussain, Tooba Mahboob (2013), “Corniculatin A, a new flavonoidal glucoside from Oxalis corniculata”, Revista Brasileira de Farmacognosia, 23(4), pp: 630-634. [2] Đỗ Tất Lợi (2005), Những cây thuốc và vị thuốc Việt Nam, Nxb. Y học, Hà Nội, pp. 236-237. [3] Merugu Srikanth, Tadigotla Swetha, Veeresh B (2012), “Phytochemistry and pharmacology of Oxalis corniculata Linn: A review”, International journal of pharmaceutical sciences and research, 3(11), pp: 4077-4085. [4] Muhammad Rashid Khan , Hina Zehra (2013), “Amelioration of CCl4-induced nephrotoxicity by Oxalis corniculata in rat”, Experimental and Toxicologic Pathology, 65(3), pp: 327–334. [5] Kirti Sheth, Philip Catalfomo, Leo A. Sciuchetti (1967), "Isolation and identification of eburicoic acid from Fomes pinicola", Journal of Pharmaceutical Sciences 56(12), pp.1656-1658. [6] Faheem Amir, Yen Chin Koay and Wan Sinn Yam (2012), "Chemical Constituents and Biological Properties of the Marine Soft Coral Nephthea", Tropical Journal of Pharmaceutical Research, 11 (3): 499-517 [7] Rebamang A. Mosa, Adebola O. Oyedeji, Francis O. Shode, Mogie Singh and Andy R. Opoku (2011), "Triterpenes from the stem bark of Protorhus longifolia exhibit anti-platelet aggregation activity", African Journal of Pharmacy and Pharmacology, 5(24), pp. 2698-2714.